NAFTA Tax Law and Policy : Resolving the Clash between Economic and Sovereignty Interests - Cockfield, Arthur J. (Book collections on Project MUSE., 2005)
In NAFTA Tax Law and Policy, Arthur J. Cockfield analyzes these different tax systems and proposes a number of recommendations to reduce the harm caused by these barriers.